Fundamentals of Acoustic Cytometry. Issue 1 (16th April 2018) - Ward, Michael D.; Kaduchak, Gregory
Abstract: Acoustic cytometry uses radiation pressure forces instead of or in addition to hydrodynamic focusing to position cells or particles in a flowing stream for analysis. Commercial implementations to date combine both hydrodynamic and acoustic focusing together to enable high precision analysis of a broad dynamic range of volumetric sample input rates up to an order of magnitude higher than is practical with hydrodynamic focus alone. This capability allows great flexibility in reducing assay time or modifying or eliminating concentration requirements or concentration steps in sample preparation protocols. It also provides a practical method for processing sub‐microliter volumes using sample dilution. In order to take full advantage of this dynamic range, it is necessary to understand the fundamental benefits and limitations of acoustic focusing as applied to flow cytometry. © 2018 by John Wiley & Sons, Inc.